In‐phase zero TE musculoskeletal imaging. Issue 1 (20th August 2019) - Engström, Mathias; McKinnon, Graeme; Cozzini, Cristina; Wiesinger, Florian
Abstract : Purpose: To introduce a new method for in‐phase zero TE (ipZTE) musculoskeletal MR imaging. Methods: ZTE is a 3D radial imaging method, which is sensitive to chemical shift off‐resonance signal interference, especially around fat–water tissue interfaces. The ipZTE method addresses this fat–water chemical shift artifact by acquiring each 3D radial spoke at least twice with varying readout gradient amplitude and hence varying effective sampling time. Using k‐space‐based chemical shift decomposition, the acquired data is then reconstructed into an in‐phase ZTE image and an out‐of‐phase disturbance. Results: The ipZTE method was tested for knee, pelvis, brain, and whole‐body. The obtained images demonstrate exceptional soft‐tissue uniformity free from out‐of‐phase disturbances apparent in the original ZTE images. The chemical shift decomposition was found to improve SNR at the cost of reduced image resolution. Conclusion: The ipZTE method can be used as an averaging mechanism to eliminate fat–water chemical shift artifacts and improve SNR. The method is expected to improve ZTE‐based musculoskeletal imaging and pseudo CT conversion as required for PET/MR attenuation correction and MR‐guided radiation therapy planning.